The pro-tumorigenic cytokine IL-32 has a high turnover in multiple myeloma cells due to proteolysis regulated by oxygen-sensing cysteine dioxygenase and deubiquitinating enzymes - Kastnes, Martin; Aass, Kristin Roseth; Bouma, Siri Anshushaug; Årseth, Charlotte; Zahoor, Muhammad; Yurchenko, Mariia; Standal, Therese (Frontiers in Oncology, 2023)
IL-32 is a pro-inflammatory cytokine expressed by several types of cancer cells and immune cells. Currently no treatment targeting IL-32 is available and its intracellular and exosomal localization makes IL-32 less accessible to drugs. We previously showed that hypoxia promotes IL-32 expression through HIF1in multiple myeloma cells. Here we demonstrate that high-speed translation and ubiquitin-dependent proteasomal degradation leads to a rapid IL-32 protein turnover. We find that IL-32 protein half-life is regulated by the oxygen-sensing cysteine-dioxygenase ADO and that deubiquitinases actively remove ubiquitin from IL-32 and promote protein stability. Deubiquitinase inhibitors was efficient in promoting degradation of IL-32 and may represent a strategy for reducing IL-32 levels in multiple myeloma. The fast- turnover and enzymatic deubiquitination of IL-32 is conserved in primary human T cells, thus deubiquitinase inhibitors may also affect T cell responses in various diseases.